Kepastian Hukum dalam Penetapan Kriteria Money Politik menjelang Kampanye Pemilu 2024 - Umi Khairiah; Ervina Sari Sipahutar; Irwansyah Tanjung (Fakultas Hukum Universitas Al Azhar Medan, 2023)
The implementation of elections or regional elections is very vulnerable to corruption. Money politics is the origin of political corruption. Money politics is a serious problem in elections and elections in Indonesia, starting from the election of village heads, regional heads, legislative members, and the Regional Representative Council (DPD) to the President and Vice President, it is vulnerable to the practice of buying and selling votes. One recent example of allegations of money politics was the discovery of a case of giving away milk during the CFD on December 3 2023 by Vice President Gibran which according to Bawaslu was not an election violation and the case of distributing envelopes bearing the PDIP logo at a mosque in Sumenep amounting to IDR 300 thousand. Again, Bawaslu stated that it could not investigate the case in terms of violations of money politics provisions. This is because the Election Law only regulates the prohibition of money politics during the campaign period. Therefore, there needs to be a clear determination in determining the criteria for money politics. The type of research used is normative juridical with a statutory approach and a conceptual approach. There is a gap for the practice of money politics to occur in the upcoming 2024 elections due to the weakness of the regulations governing money politics. This weakness is not only in terms of material, such as if there are subjects of criminal acts who are not organizers, participants, and campaign teams who practice money politics during the campaign and quiet periods, then these perpetrators cannot be punished under the Election Law. Only election organizers, participants, and campaign teams are prohibited from engaging in money politics. Transactions giving money are sometimes not carried out by candidates directly but through intermediaries with the success team or parties who have an interest in the candidate. Legal uncertainty was also seen during the campaign period which only lasted 75 days. So if forms of money politics are carried out by candidates and their teams outside the campaign period, they are not included in the category of money politics